Electricity generation from renewable energy based on abandoned wind fan - Arni Munira Markom; Muhammad Hakimi Aiman Hadri; Tuah Zayan Muhamad Yazid; Zakiah Mohd Yusof; Marni Azira Markom; Ahmad Razif Muhammad (Institute of Advanced Engineering and Science, 2022)
In the 21st century, our world is facing difficult conditions for serious environmental pollution and the problem of energy shortage. An innovative idea has emerged to recycle wind energy from air conditioning condenser fans in outdoor buildings. Therefore, the main goal of this research is to develop renewable wind energy from the condenser fan of an air conditioner using Arduino as a microcontroller. This research moves towards a portable, low cost, environmentally friendly mini device that harnesses renewable energies with endless resources for future alternative power generation and reduces the burden of consumers' electricity bills.